Internal Control Systems in Nepal: A Case of Nepal Telecom - Ballav Niroula; Achut Gyawali (Jambura Science of Management, 2021)
The purpose of this study is to discover the efficacy of internal control system of Nepal Telecom. This study followed a case study research design, because it offers a deeper perspective and clearer understanding of the internal control system and its practices. The sample size of this study consisted of all the employees working at different level in Nepal Telecom. The convenience sampling method has been applied for selection of respondents. The researchers distributed 280 questionnaires out of them only 240 respondents returned usable questionnaires. This study was totally based on primary data. In order to make proper analysis descriptive and inferential statistics were used using SPSS software version 23. The finding of this study showed that the control environment, risk assessment, control activities, communication and monitoring affects perceived performance of organization. Effective internal control system helped to increase working efficiency also. The recommendations were made that the company should emphasize the required internal organizational management structure to be implemented. This is because of the internal organizational management structure positively affects the execution of strategies and policies, thereby achieving a sustainable competitive advantage and increment of profit.